Analysis of the visualizing changes in radar time series using the REACTIV method through satellite imagery - Hamid, Hamood Shehab; Chisab, Raad Farhood (International Journal of Electrical and Computer Engineering (IJECE), 2022)
A visualizing temporal stack of synthetic aperture radar (SAR) images are presented in this work, the method is called REACTIV, which enabled us to highlight color zones that have undergone change over the detected period of time. This work has been widely tested using Google earth engine (GEE) platform, this method depends on the hue-saturation-value (HSV) of visualizing space and supports estimation only in the time domain; the method does not support the spatial estimation. The coefficient of temporal coefficient variation is coded depending on the saturation color, of which several statistical properties are described. The limitations are studied, and some applications are implemented in this study.